(untitled) (Journal of Comparative & International Higher Education, 2021)
Abstract Although the internationalization of higher education through the standardization of English language in academia is considered progressive in the 21st century, in the context of Lusophone universities it is perceived as a deterrent for scholars ‘career progression. In particular, the evidence of lived experiences in Mozambican universities suggests that relationship between English language competence and professional status remains inconclusive. We examine the validity of these statements, focusing on the impact of English language for career development in two Portuguese language-speaking universities. Applying the career construction theory and practice, adaptability and identity structures (Savickas, 2013), the study employs a case study design, purposive sampling and content analysis approach. The motivation behind adapting the theory is based on its fundamental premise of individual and social constructivism of knowledge, which explains the interpretative and interpersonal processes through which individuals construct themselves. The data collection methods employed are semi structured interviews with permanently employed scholars and document review at Eduardo Mondlane and Catholic universities in Mozambique. The study explores how Mozambican academic researchers adapt and establish their English language identity in career development. In revealing different experiences of English language use or perspectives across academics’ career development process, the study contributes to a comparative higher education career research by guiding the formulation of language policy for career development in Lusophone countries. Key words: Language policy, Internationalization, career development, English language, Mozambique, higher education.